2019
DOI: 10.3122/jabfm.2019.01.180182
|View full text |Cite
|
Sign up to set email alerts
|

No Magic Pill: A Prescription for Enhanced Shared Decision-Making for Depression Treatment

Abstract: For over 2 decades, there have been debates, sometimes contentious, about the efficacy and safety of antidepressants. Growing awareness of the difficulty some patients have when discontinuing these medications has intensified these debates. Recently, Cipriani and colleagues published the largest meta-analysis to date that assessed the efficacy and tolerability of antidepressants. They concluded that all were more efficacious than placebo, and they also synthesized the trial results from head-to-head studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The debate whether antidepressants are an effective treatment for depression is ongoing and unresolved [1][2][3][4][5]. Although meta-analyses unequivocally produce statistically significant drugplacebo differences in acute treatment trials [6][7][8], various researchers showed that these differences are so small that their practical relevance is questionable [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The debate whether antidepressants are an effective treatment for depression is ongoing and unresolved [1][2][3][4][5]. Although meta-analyses unequivocally produce statistically significant drugplacebo differences in acute treatment trials [6][7][8], various researchers showed that these differences are so small that their practical relevance is questionable [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…10 A recent commentary offers suggestions for helping physicians in primary care settings address depression treatment options and uncertainties. 11 There is limited evidence on how involved people are with the decision to treat their depression and the factors that influence whether or not the decision aligns with the patients' values and preferences. Results from a meta-analysis of patient preferences for psychiatric disorders reported that overwhelmingly patients prefer psychological treatment compared with pharmacologic treatment.…”
mentioning
confidence: 99%